2020
DOI: 10.3390/ma13235521
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Strength Reliability of Impregnated Wood after High Temperature Conditions

Abstract: The paper presents the results of the research into the impact of impregnation of wood on its bending strength and elastic modulus under normal conditions and after thermal treatment and investigates its structural reliability. Pinewood, non-impregnated and pressure impregnated with a solution with SiO2 nanoparticles, was used in this research. The use of nanoparticles decreases the flammability of timber among others. Some of the tested samples were treated at 250 °C. This temperature corresponds to the bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…The findings of this paper regarding the future of pressure-impregnated wood and modified wood, highly processed surface treatment products, bio-based binders, environmentally friendly methods of wood preservation, and fire protection strategies confirmed some of the findings reported in other studies, such as [64][65][66][67][68].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The findings of this paper regarding the future of pressure-impregnated wood and modified wood, highly processed surface treatment products, bio-based binders, environmentally friendly methods of wood preservation, and fire protection strategies confirmed some of the findings reported in other studies, such as [64][65][66][67][68].…”
Section: Discussionsupporting
confidence: 85%
“…In the interviews, expert responses indicated that pressure-impregnated wood will continuously develop and secure its market in the future in Finland. Many innovative studies (e.g., [64,69]) on this subject in the literature support this finding. Additionally, expert opinions emphasized that the new wood preservation methods introduced are not economical and require long-term research and testing.…”
Section: Discussionsupporting
confidence: 52%
“…In addition to adhering to the International Building Code [5] and relevant national regulations, enhancing the fire resistance of construction materials is imperative. Thus, mitigating the fire hazard associated with wooden structures emerges as a primary obstacle to expanding timber's utilization in construction [6]. During fires, timber structures experience diminished loadbearing capacity compared with non-combustible materials such as steel, accompanied by decohesion attributable to carbonization and the thermal breakdown of biopolymers including cellulose, hemicellulose, and lignin.…”
Section: Introductionmentioning
confidence: 99%
“…The protection of functional wood, particularly that coming into direct contact with water or soil, is largely based on introducing protection agents with powerful, conserving, fungicidal properties. The range of such products is constantly being expanded with the introduction of new generations of active substances, which are currently being developed with regard to eco-safety requirements [1][2][3][4][5]. Generally speaking, wood impregnation processes are carried out by surface methods (lubrication, spraying and immersion) or vacuum pressure methods.…”
Section: Introductionmentioning
confidence: 99%